Short-term effect of 4% hypertonic glucose as compared to 4% mixed hypertonic mannitol solution in conventional peritoneal dialysis - S. Phanichphant (2018)
16 peritoneal dialyses were performed in 14 end-stage kidney disease patients; 6 had diabetic nephropathy, and, of the nondiabetic group, 7 had chronic glomerulonephritis, and 1 had polycystic kidney disease. The peritoneal dialysis performed with conventional 1.5% glucose solution, intervened by four consecutive exchanges using 4% hypertonic glucose solution, was compared to 4% mixed hypertonic mannitol solution in the diabetic and nondiabetic group. There was no significant change of serum glucose, when postdialysis with 1.5% glucose solution was compared to 4% mixed hypertonic mannitol solution; however there was a significant change of serum osmolality in both groups. Postdialysis with both 4% hypertonic solutions showed that there was no significant difference of ultrafiltration volume in both groups of patients, but there was a significant difference in serum glucose in the diabetic group. The transport mechanism of mixed hypertonic mannitol solution as compared to hypertonic glucose solution is discussed. The application of hypertonic mannitol solution for clinical use is not advised.